Upaya Penguatan Kurikulum Pembelajaran Pendidikan Agama Islam Berbasis Moderasi Beragama - Riskun Iqbal (Journal on Education, 2023)
This study means to look at the Endeavors to Reinforce the Learning Educational program of Islamic Strict Schooling In view of Strict Control. This examination was composed in view of writing audit and top to bottom comprehension and gathered understanding from different believed essential book sources. This sort of exploration is subjective with a library research approach. Information assortment strategies are completed with documentation. Wellsprings of information come from books and diaries. The information investigation procedure utilizes content examination. The consequences of the review demonstrate the way that fortifying strict control should be possible through a praiseworthy based instructive educational program that moves philosophical qualities to understudies. The upsides of strict control ought to constantly be imparted in strict individuals with the goal that they can be lenient, fair and adjusted in building inner relations among individuals of various religions and outer relations between individuals of various religions. In this way, instructive foundations are expected to assume a functioning part in endeavors to assimilate strict control with the goal that understudies can execute these qualities in public activity. Furthermore, instructive foundations must continually screen and assess the improvement of their understudies as a work to forestall deradicalization of the universe of training. The learning of Islamic strict instruction should underline social schooling, establishing strict balance which centers around the primary objective of regarding others and oneself. As well as being educated on worldwide issues while as yet focusing on moderate and open minded esteems and showing Rahmatan lil 'alamin attributes.